2022
DOI: 10.15294/physcomm.v6i2.36755
|View full text |Cite
|
Sign up to set email alerts
|

Pancasila Student Profiles in Science Lessons and Potential for Strengthening by Developing PjBL-Based E-Modules

Abstract: This study aims to find out class VII students’ profiles of Pancasila abilities of MTs SA Miftahul Huda Bumijawa. The dimensions of the meticulous Pancasila student profiles include four dimensions, namely critical reasoning, creativity, mutual cooperation, and independence. This type of research is a qualitative descriptive. Data collection instrument were observation and interview guidelines. Based on research data, the results showed that the ability of students to the Pancasila student profiles were still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Strengthening the dimensions of the Pancasila student profile needs to implement the project learning model. project-based learning that can develop soft skills and build the character of Pancasila students in students (Imania et al, 2022).…”
Section: Mutual Cooperationmentioning
confidence: 99%
“…Strengthening the dimensions of the Pancasila student profile needs to implement the project learning model. project-based learning that can develop soft skills and build the character of Pancasila students in students (Imania et al, 2022).…”
Section: Mutual Cooperationmentioning
confidence: 99%
“…Research (Syofyan et al 2022) measured the dimensions of the Pancasila learner profile in PGSD students in science learning and found that the dimensions of the Pancasila learner profile in students are truth to God Almighty and an attitude of caring for the environment. However, a study carried out by (Imania et al 2022) found that the students' ability to meet the Pancasila learner profile at MTs SA Miftahul Huda Bumijawa is still very low, indicating that the applied learning media and models have not been able to strengthen the Pancasila learner profile. Pancasila learner profile in the context of biology learning may vary depending on the particular educational institution and the methods used for teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…(Rahmadani et al 2023). Creating learning activities that allow students to explore their potential without restriction is one way of implementing the independent dimension (Imania et al 2022). In the independent dimension, teachers accustom students to doing biology tasks independently, students are not allowed to discuss with other students and cheat on other students' work.…”
mentioning
confidence: 99%
See 1 more Smart Citation